Rapidly crystallized PPS modified material and preparation method thereof
By adding nucleating agent and polyphenylene sulfone resin to the polyphenylene sulfide material and combining it with PPSU, the problems of slow crystallization rate and low glass transition temperature during molding of the polyphenylene sulfide material are solved, and a rapid crystallization and high-performance polyphenylene sulfide modified material is achieved.
Patent Information
- Application Number
- CN202411671441.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The existing polyphenylene sulfide materials have a slow crystallization rate and a low glass transition temperature during molding, resulting in low crystallinity of molded products, low performance, and require annealing to improve crystallinity, which is time-consuming and labor-intensive.
By adding a nucleating agent and blending it with polyphenylene sulfone resin and additives, the glass transition temperature and crystallization rate of the PPS material are increased, and a product with high crystallinity and performance is directly formed.
The rapid crystallization of polyphenylene sulfide material is achieved, the glass transition temperature and crystallization rate of the material are improved, and the product can achieve the target performance without annealing, shorten the molding time and improve production efficiency.
Smart Images

Figure BDA0005145958170000021 
Figure BDA0005145958170000061 
Figure BDA0005145958170000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a fast-crystallizing PPS modified material and a preparation method thereof. Background Art
[0002] Among high-performance thermoplastic engineering plastics, polyphenylene sulfide has developed rapidly since its industrial production in the 1980s due to its excellent thermal stability, chemical stability, dimensional stability, corrosion resistance and electrical properties, good mechanical properties, bonding properties, and excellent flame retardancy. It has been widely used in automobile manufacturing, electronics and electrical, chemical industry, instrumentation, etc.
[0003] The molecular structure of polyphenylene sulfide determines that it has the disadvantages of high brittleness and poor toughness when directly molded into products, which greatly limits the application of polyphenylene sulfide; therefore, in conventional applications, the target performance of the product is obtained by designing the product molding process or modifying polyphenylene sulfide. For example, the glass transition temperature of polyphenylene sulfide is about 90°C, the crystallization temperature is about 125°C, and the crystallization rate is relatively slow; in order to ensure the performance of the product, on the one hand, molding can be used to obtain the preformed product at a high mold temperature and a long molding time, and then annealing treatment, otherwise the crystallization of the polyphenylene sulfide material is not perfect when it is molded, and the molecular chain segments of the molded product will re-stretch and arrange to creep when subjected to external force, and the product will have a large deformation, which seriously affects the subsequent use of the product; on the other hand, the performance of polyphenylene sulfide material products can be improved by glass fiber composite, rubber elastomer toughening or high-performance engineering plastic blending, such as higher strength, high temperature stability and dimensional stability.
[0004] The above-mentioned method of using process improvement to ensure the performance of polyphenylene sulfide products is time-consuming and laborious. Currently, due to the limitations of molding equipment, many companies find it difficult to ensure that the temperature of the mold reaches 130°C. It is difficult to achieve molding conditions of 130-180°C, resulting in a high rate of unqualified molded products. The method of modifying polyphenylene sulfide to obtain composite materials to obtain functional films, coatings and composite materials further expands the application range of polyphenylene sulfide and achieves breakthrough success in the fields of electronics, aerospace, automobile transportation, etc. Therefore, it is also possible to modify polyphenylene sulfide to increase the crystallization temperature and crystallization rate, so that the target performance product can be obtained without annealing when molding the product. Summary of the invention
[0005] The object of the present invention is to provide a fast-crystallizing PPS modified material and a preparation method thereof. The method prepares the fast-crystallizing PPS modified material by adding a nucleating agent and blending it with a polyphenylene sulfone resin and an auxiliary agent, thereby improving the glass transition temperature and crystallization rate of PPS, and the product meets the performance standards without annealing.
[0006] To achieve the above object, the present invention proposes the following technical solutions:
[0007] In the first aspect, a fast crystallizing PPS modified material is provided, which comprises, by weight:
[0008]
[0009] Furthermore, the polyphenylene sulfide has a melt index of 300 to 400 g / 10 min.
[0010] Furthermore, the reinforcing filler is selected from strip-shaped glass fibers, and the average length of the glass fibers is 1 to 5 mm.
[0011] Furthermore, the nucleating agent is selected from nano-SiO2, talc, barium sulfate, wollastonite, attapulgite, diatomaceous earth or hydrotalcite; wherein the size of the nano-SiO2 is 50 to 500 nm, and the size of the talc is 5000 to 8000 mesh.
[0012] Furthermore, the auxiliary agent includes a lubricant and an antioxidant; the lubricant is selected from a combination of any one or more of calcium stearate, silicone powder, and ethylene bisstearamide; the antioxidant is selected from a combination of one or more of antioxidant 1010, antioxidant 1098, and antioxidant 168.
[0013] Furthermore, the weight average molecular weight of the polyphenylene sulfone resin is 30,000 to 60,000D.
[0014] Furthermore, the invention further comprises, by weight: 1 to 2 parts of thermotropic liquid crystal polymer; the thermotropic liquid crystal polymer is S-TLCP.
[0015] Secondly, a fast-crystallizing PPS modified material is proposed, comprising the following steps: blending polyphenylene sulfide, polyphenylene sulfone resin, a nucleating agent and an auxiliary agent, and then adding a reinforcing filler thereto for extrusion granulation to obtain a fast-crystallizing PPS modified material.
[0016] Furthermore, the blending temperature is 100-120° C., and the blending time is 50-70 min.
[0017] Furthermore, the temperature of the extrusion granulation is 270-320°C.
[0018] It can be seen from the above technical solutions that the technical solutions of the present invention have the following beneficial effects:
[0019] The invention discloses a fast-crystallizing PPS modified material and a preparation method thereof. The material comprises, by weight: 70 to 90 parts of polyphenylene sulfide; 5 to 15 parts of polyphenylene sulfone resin; 35 to 45 parts of reinforcing filler; 1 to 3 parts of nucleating agent; and 2 to 5 parts of auxiliary agent. During preparation, polyphenylene sulfide, polyphenylene sulfone resin, nucleating agent and auxiliary agent are first blended, and then reinforcing filler is added thereto for extrusion granulation to obtain a fast-crystallizing PPS modified material. The fast-crystallizing PPS modified material of the invention changes the nucleation mode of PPS to differential phase nucleation by adding a nucleating agent and compounding with PPSU, thereby greatly improving the crystallization rate of the modified material and the crystallinity. At the same time, the glass transition temperature of the pure PPS phase is increased from the original 90 to 110°C to 130 to 150°C by compounding PPS / PPSU. The final product is dimensionally stable, and its crystallinity and toughness can directly reach the performance of the parts after the product is formed, without the need for annealing and recrystallization.
[0020] The present invention also improves the compatibility between PPS, PPSU and the reinforcing material by introducing S-TLCP into the formula of the modified material, thereby synergistically improving the mechanical properties and crystallization rate of the PPS modified material.
[0021] It should be appreciated that all combinations of the foregoing concepts, as well as additional concepts described in greater detail below, may be considered to be part of the inventive subject matter of the present disclosure, provided such concepts are not mutually inconsistent.
[0022] The foregoing and other aspects, embodiments and features of the present invention can be more fully understood in conjunction with the following description. Other additional aspects of the present invention, such as the features and / or beneficial effects of the exemplary embodiments, will be apparent from the following description or learned from the practice of the specific embodiments according to the present invention. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme of the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.
[0024] The words "first", "second" and similar words used in the patent application specification and claims of the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. Similarly, unless the context clearly indicates otherwise, the singular form of "a", "an" or "the" and other similar words do not indicate a quantitative limitation, but indicate the existence of at least one. "Include" or "comprises" and other similar words mean that the elements or objects appearing before "include" or "comprises" include the features, wholes, steps, operations, elements and / or components listed after "include" or "comprises", and do not exclude the existence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections.
[0025] Based on the fact that the PPS modified products on the market have a slow crystallization speed and a low glass transition temperature, many products still have a low crystallinity after molding, and thus the product performance is not high, especially in terms of tensile performance and impact performance, and the product toughness is very poor and brittle; and because the PPS material is not completely crystallized, the size of the product often cannot meet the requirements of the parts and cannot be used. At present, many manufacturers use annealing and recrystallization to increase the crystallinity of the product to improve the product performance; in the conventional annealing method, the annealing temperature is generally around 180°C, and the time is 48h or more, which is not only time-consuming but also energy-consuming. Therefore, the present invention aims to propose a fast-crystallizing PPS modified material and a preparation method thereof, and by improving the formula of the PPS modified material, the product molding thereof is not only dimensionally stable, but also can meet the target use requirements without annealing and recrystallization.
[0026] Specifically, the fast crystallizing PPS modified material disclosed in the present invention comprises, by weight: 70 to 90 parts of polyphenylene sulfide; 5 to 15 parts of polyphenylene sulfone resin; 35 to 45 parts of reinforcing filler; 1 to 3 parts of nucleating agent; and 2 to 5 parts of auxiliary agent.
[0027] The polyphenylene sulfide has a melt index of 300 to 400 g / 10 min, and the weight-average molecular weight of the polyphenylene sulfone resin is 30,000 to 60,000 D; the reinforcing filler is strip-shaped glass fiber, the average length of the glass fiber is 1 to 5 mm, and it is a needle-like structure; the nucleating agent is selected from nano-SiO2, talc, barium sulfate, wollastonite, attapulgite, diatomaceous earth or hydrotalcite; the size of the nano-SiO2 is 50 to 500 nm, and the size of the talc is 5000 to 8000 mesh; the auxiliary agent includes a lubricant and an antioxidant; the lubricant is selected from a combination of any one or more of calcium stearate, silicone powder, and ethylene bisstearamide; the antioxidant is selected from a combination of one or more of antioxidant 1010, antioxidant 1098, and antioxidant 168.
[0028] The fast crystallizing PPS modified material disclosed in the present invention further comprises, by weight, 1 to 2 parts of a thermotropic liquid crystal polymer; the thermotropic liquid crystal polymer is S-TLCP, such as HBA / HNA thermotropic liquid crystal polyarylate.
[0029] During preparation, the fast crystallized PPS modified material includes the following steps: blending polyphenylene sulfide, polyphenylene sulfone resin, nucleating agent and auxiliary agent at a temperature of 100 to 120° C. for 50 to 70 minutes, and then adding reinforcing filler thereto for extrusion granulation to obtain the fast crystallized PPS modified material; wherein the extrusion granulation temperature is 270 to 320° C. When the thermotropic liquid crystal polymer is added to the modified material, the thermotropic liquid crystal polymer is synchronously blended with polyphenylene sulfide, polyphenylene sulfone resin and the like.
[0030] The following is a further detailed introduction to the fast crystallizing PPS modified material and its preparation method disclosed in the present invention in conjunction with specific embodiments. In which, the polyphenylene sulfide is selected as injection-molding grade linear polyphenylene sulfide with a melt index of 350g / 10min; the polyphenylene sulfone resin is selected as Solvay 5100 from the United States, and the glass fiber is alkali-free glass fiber.
[0031] Example 1
[0032] A fast-crystallizing PPS modified material comprises, by weight: 80 parts of polyphenylene sulfide; 10 parts of polyphenylene sulfone resin; 40 parts of reinforcing filler; 2 parts of nucleating agent; 2 parts of lubricant; and 2 parts of antioxidant; wherein the polyphenylene sulfide has a melt index of 350 g / 10 min, and the weight average molecular weight of the polyphenylene sulfone resin is 40000D; the reinforcing filler is a strip of glass fiber, and the average length of the glass fiber is 2 mm; the nucleating agent is a nano-SiO2 with a size of 200 nm; the lubricant is calcium stearate, and the antioxidant is antioxidant 1010. During preparation, polyphenylene sulfide, polyphenylene sulfone resin, nucleating agent, lubricant and antioxidant are firstly blended at a temperature of 240° C. for 60 minutes, and then glass fiber is added thereto and extruded and granulated at a temperature of 310° C. to obtain the fast-crystallizing PPS modified material.
[0033] The difference between Examples 2-10 and Example 1 is only that the ratio of the formula components for preparing the rapidly crystallized PPS modified material and the characteristics of the selected components are different, and the process parameters of other preparation processes are the same, as shown in Table 1. The difference between Comparative Examples 1-5 and Example 1 is only that the ratio of the core components of the formula for preparing the rapidly crystallized PPS modified material is different.
[0034] Table 1 Formula composition data of Examples 2-10, Comparative Examples 1-5 and Example 1
[0035]
[0036] The properties of the PPS modified materials obtained in Examples 1-10 and Comparative Examples 1-5 were tested in the following manner:
[0037] Mechanical properties test:
[0038] The tensile properties of the standard samples of the fast-crystallized PPS modified materials obtained in Examples 1-10 and Comparative Examples 1-5 were tested according to GB1447-83 standard at a tensile rate of 10 mm / min; the bending properties were tested according to GB / T9341-2008 standard; and the cantilever beam notched impact strength was tested according to GB1043-2008 standard.
[0039] Crystallization performance test: tested with Mettler-Toledo differential scanning calorimeter (DSC), test conditions: 50-350°C, heating rate 10°C / min, keeping warm for 3min, 350-50°C cooling rate 20°C / min, obtain crystallization temperature (°C), crystallization peak half-width and crystallization enthalpy (J / g) according to the DSC spectrum; the higher the crystallization temperature of the material, the faster its crystallization rate and the better the processing performance.
[0040] Table 2 Performance data of PPS modified materials obtained from Examples 1-10 and Comparative Examples 1-5
[0041]
[0042] The test results are shown in Table 2. It can be seen from the table that the tensile strength, flexural strength and Izod notched impact strength of the PPS modified materials obtained in Examples 1-10 are increased compared with Comparative Examples 1-3, that is, the modified materials to which polyphenylene sulfone resin and glass fiber are added separately have higher strength and toughness, and the compounding and reinforcing effect is better. In addition, when S-TLCP is added as a compatibilizer in Example 2 and Comparative Example 2, the mechanical properties of the modified materials are further improved, and they play a synergistic compatibility role when compounded with PPSU and glass fiber, and by improving the interfacial force of the PPS / PPSU / glass fiber modified materials, the mechanical properties of the modified materials are improved while the crystallization properties are further improved.
[0043] It is obvious from Example 1 and Comparative Example 1 that by introducing a small amount of the polyphenylene sulfone resin into the pure PPS resin system, the glass transition temperature is increased from 109°C to 147°C, the crystallization temperature is increased from 195°C to 236°C, an increase of 41°C, and the half-peak width of the crystallization is also significantly narrowed, directly shortened from 9.8 to 6.1, indicating that the polyphenylene sulfone resin has a significant effect on improving the crystallization ability of the fiber-reinforced PPS material and accelerating its crystallization rate; the reason is that the pure PPS material is homogeneous nucleation during crystallization, and the nucleation rate is slow, resulting in a low crystallization rate. The introduction of PPSU nucleation mode changes to heterogeneous nucleation, and by adding a nucleating agent, the crystallization rate of the product can be greatly improved, and finally the product crystallinity and toughness can achieve the performance of the parts without annealing. Combining Example 2 and Comparative Example 2, it can be concluded that adding S-TLCP to the formula can significantly improve the crystallization performance of the fiber-reinforced PPS composite material, and the improvement effect of S-TLCP and polyphenylene sulfone resin on the pure fiber-reinforced system is more obvious; in addition, it can be concluded from Examples 3-10 and Comparative Examples 3-5 that the nucleating agent in the present application can cooperate with the strip-shaped glass fiber to show a better crystallization performance improvement effect on the PPS modified material. In addition, in the specific application of the material of this scheme, corresponding color powder can be added to the formula according to customer needs to obtain PPS modified materials with the color required by customers.
[0044] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.
Claims
1. A fast crystallizing PPS modified material, characterized in that: In parts by weight, including:
2. The fast crystallized PPS modified material according to claim 1, characterized in that: The polyphenylene sulfide has a melt index of 300 to 400 g / 10 min.
3. The fast crystallized PPS modified material according to claim 1, characterized in that: The reinforcing filler is selected from strip-shaped glass fibers, and the average length of the glass fibers is 1 to 5 mm.
4. The fast crystallized PPS modified material according to claim 1, characterized in that: The nucleating agent is selected from nano-SiO2, talc, barium sulfate, wollastonite, attapulgite, diatomaceous earth or hydrotalcite; Wherein, the size of the nano-SiO2 is 50-500nm, and the size of the talc powder is 5000-8000 mesh.
5. The fast crystallized PPS modified material according to claim 1, characterized in that: The auxiliary agent includes a lubricant and an antioxidant; The lubricant is selected from a combination of any one or more of calcium stearate, silicone powder, and ethylene bisstearamide; the antioxidant is selected from a combination of one or more of antioxidant 1010, antioxidant 1098, and antioxidant 168.
6. The fast crystallized PPS modified material according to claim 1, characterized in that: The weight average molecular weight of the polyphenylene sulfone resin is 30,000 to 60,000D.
7. The fast crystallized PPS modified material according to claim 1, characterized in that: In terms of weight, it also includes: 1 to 2 parts of thermotropic liquid crystal polymer; the thermotropic liquid crystal polymer is S-TLCP.
8. A fast crystallizing PPS modified material, characterized in that: The method comprises the following steps: blending polyphenylene sulfide, polyphenylene sulfone resin, a nucleating agent and an auxiliary agent, adding a reinforcing filler therein, performing extrusion granulation, and obtaining a fast-crystallized PPS modified material.
9. The fast crystallized PPS modified material according to claim 8, characterized in that: The blending temperature is 100-120° C., and the blending time is 50-70 minutes.
10. The fast crystallized PPS modified material according to claim 9, characterized in that: The temperature of the extrusion granulation is 270-320°C.
Citation Information
Patent Citations
A polyether sulphone / polyphenylene sulfide alloy, and a preparing method and application thereof
CN109777106A
Polymer alloy comprising a sulphur-containing aromatic polymer and a thermoplastic vulcanizate
CN110612330A
High-crystallinity polyphenylene sulfide composite material easy for machining shaping, preparation method and application thereof
CN110903650A
Glass-filed polymer composition comprising a poly(aryl ether sulfone), a poly(aryl ether ketone), at least one polyphenylene sulfide and glass fibers
CN111032783A
Polyarylene sulfide film
CN111819246A